2016
DOI: 10.1038/bjc.2016.171
|View full text |Cite
|
Sign up to set email alerts
|

Tumour and immune cell dynamics explain the PSA bounce after prostate cancer brachytherapy

Abstract: Background:Interstitial brachytherapy for localised prostate cancer may be followed by transient increases in prostate-specific antigen (PSA) that resolve without therapy. Such PSA bounces may be associated with an improved outcome but often cause alarm in the patient and physician, and have defied explanation.Methods:We developed a mathematical model to capture the interactions between the tumour, radiation and anti-tumour immune response. The model was fitted to data from a large cohort of patients treated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The mechanisms underlying PSA bounce and its association with age have not been fully elucidated. However, Yamamoto et al demonstrated an increase in tumor-infiltrative CD3 and cytotoxic CD8 cells in bounce-positive patients [18], seemingly explaining the higher incidence of PSA bounce in younger (i.e., more immunocompetent) patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying PSA bounce and its association with age have not been fully elucidated. However, Yamamoto et al demonstrated an increase in tumor-infiltrative CD3 and cytotoxic CD8 cells in bounce-positive patients [18], seemingly explaining the higher incidence of PSA bounce in younger (i.e., more immunocompetent) patients.…”
Section: Discussionmentioning
confidence: 99%
“…CIRT was initiated on day 0. PSA was measured at 1,2,3,6,9,12,15,18,21,24,30,36,42,48,54, and 60 months post-CIRT at Gunma University Hospital. PSA bounce was defined as an increase in PSA over a cutoff followed by a spontaneous decrease to or below the pre-bounce nadir [17].…”
Section: Psa Assessmentmentioning
confidence: 99%
“…Spatial distribution of cytotoxic T cells in proximity to cancer cells has just recently been demonstrated to correlate with increased overall survival of patients with pancreatic cancer . Like the dynamics of immune reaction against tumors, infiltration of immune cells into tumors takes place . Hettich and colleagues demonstrated that irradiation with 2×12 Gy on consecutive days of B16 melanoma tumors induces a high infiltration of CD8+ T cells at day 5 after the last irradiation.…”
Section: Immunological Basis For Design Of Multimodal Radio‐immunothementioning
confidence: 99%
“…131 Like the dynamics of immune reaction against tumors, 132 infiltration of immune cells into tumors takes place. 133 Hettich and colleagues demonstrated that irradiation with 2×12 Gy on consecutive days of B16 melanoma tumors induces a high infiltration of CD8+ T cells at day 5 after the last irradiation. The presence of the cytotoxic T cells in the tumor was, however, limited since later on the amount of these adaptive immune cells dropped again.…”
Section: Dynamics Of Immune Cell Infiltrationmentioning
confidence: 99%
“…Although a treatment failure is traditionally defined using prostate specific antigen (PSA) through the Phoenix criteria as the nadir þ 2 ng/mL, a phenomenon was observed after brachytherapy in which a nonfailure interval PSA climbs by a value less than 2 ng/mL and then returns to the prerise PSA or below, which was coined by Wallner as PSA ''bounce.'' (9) Although the exact pathophysiologic significance of the bounce phenomenon is unclear, recent evidence suggests that it may be related to an increased T-cell response to the tumor (10). Several studies have analyzed the predictive and prognostic significance of the PSA bounce.…”
Section: Introductionmentioning
confidence: 99%